2010
DOI: 10.1016/j.fishres.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and growth of Atlantic cod (Gadus morhua L.) along a latitudinal gradient

Abstract: Havforskningsinstituttets institusjonelle arkiv Brage IMR - Institutional repository of the Institute of Marine Research b r a g e i m rDette er forfatters siste versjon av den fagfellevurderte artikkelen, vanligvis omtalt som postprint. I Brage IMR er denne artikkelen ikke publisert med forlagets layout fordi forlaget ikke tillater dette. Du finner lenke til forlagets versjon i Brage-posten. Det anbefales at referanser til artikkelen hentes fra forlagets side. Ved lenking til artikkelen skal det lenkes til po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…However, results within the current study and collectively with earlier work and the multiple Grand Bank studies provide support for decreasing fecundity with increasing latitude as has been demonstrated in other species and regions (e.g. Thorsen et al, 2010).…”
Section: Tablesupporting
confidence: 88%
“…However, results within the current study and collectively with earlier work and the multiple Grand Bank studies provide support for decreasing fecundity with increasing latitude as has been demonstrated in other species and regions (e.g. Thorsen et al, 2010).…”
Section: Tablesupporting
confidence: 88%
“…Size specific fecundity varies amongst populations due to adaptations to local environmental conditions, both abiotic (e.g. salinity and temperature; Nissling and Dahlman, 2010;Thorsen et al, 2010) and biotic (food availability and population density; Nash et al, 2000;Kennedy et al, 2007), and temporally with fish size/age and condition, i.e. with the stock structure within a population (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic cod [72]; black scabbardfish Aphanopus carbo Lowe, 1839 [14,50]; and European seabass Dicentrarchus labrax (Linnaeus, 1758) [43]), and it is assumed that species with determinate fecundity are strongly associated with capital breeding behaviour [44]. In determinate species, the reproductive investment is heavily dependent on the feeding season prior to the major yolk production that takes place during vitellogenesis [5]; however, batch spawning can reduce the energy initially required for spawning [44].…”
Section: Discussionmentioning
confidence: 99%